(untitled) (CIPEEX, 2024)
QUALITY OF LIFE (QOL) IS A WIDELY DISCUSSED TOPIC ACROSS ALL AGE GROUPS, ENCOMPASSING SPIRITUAL, MENTAL, PHYSICAL, EMOTIONAL, AND SOCIAL RELATIONSHIP ASPECTS AS DEFINED BY THE WORLD HEALTH ORGANIZATION (WHO). THE OBJECTIVE OF THIS STUDY WAS TO ASSESS THE WELL-BEING OF ADOLESCENTS BY INVESTIGATING THE KEY FACTORS THAT POSITIVELY OR NEGATIVELY IMPACT THEIR QUALITY OF LIFE. THE RESEARCH INSTRUMENT USED WAS THE KIDDO-KINDL QUESTIONNAIRE THROUGH GOOGLE FORMS, ADMINISTERED ONLINE VIA A WHATSAPP LINK TO 30 ADOLESCENTS AGED 12 TO 16 FROM FIVE CITIES IN THE VALE DO SÃO PATRCIO REGION. IN THE ANALYSIS OF THE DATA, CONCERNING PHYSICAL HEALTH, IT WAS NOTED THAT MOST CHILDREN SOMETIMES FEEL UNWELL, TIRED, OR EXPERIENCE SOME FORM OF DISCOMFORT, WHICH CAN NEGATIVELY INFLUENCE THEIR QOL. IT IS PRESUMED THAT COMPLAINTS OF PHYSICAL DISCOMFORT MAY REFLECT EXPOSURE TO DEMANDING DAILY ACTIVITIES SUCH AS SCHOOL CLASSES, SPORTS PRACTICES, AND OTHER SOCIAL COMMITMENTS. IN CONTRAST TO FINDINGS RELATED TO PHYSICAL HEALTH, A SIGNIFICANT NUMBER OF CHILDREN ALSO REPORTED HAVING A LOT OF FUN AND FREQUENTLY SMILING. THIS OBSERVATION CAN BE SEEN AS A POSITIVE INDICATOR OF QOL, AS THE ABILITY TO HAVE FUN AND EXPERIENCE JOY IS ESSENTIAL FOR HEALTHY DEVELOPMENT AND SELF-ESTEEM. WITH REGARD TO THE FAMILY ENVIRONMENT, IT WAS OBSERVED THAT MOST RESPONDENTS REPORTED MAINTAINING A POSITIVE RELATIONSHIP WITH THEIR PARENTS, EXPRESSING A SENSE OF WELL-BEING IN THEIR HOMES AND NOT FEELING LIMITED BY THEIR PARENTAL FIGURES. THESE FINDINGS CAN HAVE POSITIVE IMPLICATIONS FOR QOL, PROMOTING HEALTHY AND BALANCED DEVELOPMENT. IN RELATION TO THE SCHOOL EXPERIENCE, MANY CHILDREN REPORTED FACING DIFFICULTIES IN COMPLETING ACTIVITIES, REVEALING THAT THEY RARELY FIND CLASSES INTERESTING AND EXPRESS CONCERNS ABOUT THE FUTURE. THESE PERCEPTIONS CAN HAVE BOTH NEGATIVE AND POSITIVE IMPLICATIONS FOR QOL. ON ONE HAND, THEY CAN GENERATE STRESS AND ANXIETY. FURTHERMORE, WORRIES ABOUT THE FUTURE CAN INCREASE PSYCHOLOGICAL PRESSURE. ON THE OTHER HAND, THESE EXPERIENCES CAN ALSO MOTIVATE THE DEVELOPMENT OF RESILIENCE SKILLS AS ADOLESCENTS LEARN TO FACE CHALLENGES. THEREFORE, IT CAN BE CONCLUDED THAT THE KIDDO-KINDL QUESTIONNAIRE PROVES TO BE A RELIABLE AND EFFECTIVE METHOD FOR ASSESSING QOL IN CHILDREN AND ADOLESCENTS, CONSIDERING BOTH INTRINSIC AND EXTRINSIC ASPECTS OF EACH INDIVIDUAL. THIS CONTRIBUTES TO A MORE COMPREHENSIVE AND ACCURATE UNDERSTANDING OF THIS FUNDAMENTAL DIMENSION OF QOL IN CHILDHOOD AND ADOLESCENCE.